Numerical investigation of aeroacoustics damping performance of a Helmholtz resonator : effects of geometry, grazing and bias flow - Wu, Gang (2021)
In this work, the effects of the grazing flow and its geometric dimensions on the aeroacoustics damping performance of a Helmholtz resonator are numerically evaluated. The grazing flow tangentially passing through the neck of the resonator is characterized by Mach number. And it is varied from 0 to 0.1. 2D numerical simulations are conducted by solving linearized Navier–Stokes equations in frequency domain via COMSOL 5.3. The numerical model is first validated by comparing with experimental and theoretical data available in literature, as a low Mach number grazing flow is present only. Good agreement is obtained. The model is then used to examine the effect of the grazing flow and the resonator geometric dimensions on transmission loss (TL) performance. Four key parameters are identified, and they include 1) the neck length, 2) neck diameter, 3) cavity volume and 4) the grazing flow Mach number. It is found that as the grazing flow Mach number is greater than 0.07, increasing the neck length leads to a decreased TL max . Same observation is found for increased cavity volume V r . Smaller Helmholtz resonator V r or shorter neck length L n is found to be involved with a larger TL max in the presence of the grazing flow. Further study is then conducted, when there is a joint bias–grazing flow. The bias flow could be injected with respect to the grazing flow in 3 different directions, 1) parallel, 2) perpendicular and 3) counter flow. The bias flow injection direction is found to lead to 5 dB transmission loss difference. Parallel or counter injection of the bias flow is showed to be associated with improved TL performance, since there are counter-rotating vortices produced in the cavity. Finally, increasing the Mach number of the grazing flow leads to the noise damping effectiveness being deteriorated in general, even in the presence of a bias flow. The present work shed lights on the aeroacoustics design of Helmholtz resonators in the presence of a grazing and bias flow.